Assessment of national dosimetry quality audits results for teletherapy machines from 1989 to 2015. (8th March 2016) - Muhammad, Wazir; Ullah, Asad; Mahmood, Khalid; Matiullah
Abstract : The purpose of this study was to ensure accuracy in radiation dose delivery, external dosimetry quality audit has an equal importance with routine dosimetry performed at clinics. To do so, dosimetry quality audit was organized by the Secondary Standard Dosimetry Laboratory (SSDL) of Pakistan Institute of Nuclear Science and Technology (PINSTECH) at the national level to investigate and minimize uncertainties involved in the measurement of absorbed dose, and to improve the accuracy of dose measurement at different radiotherapy hospitals. A total of 181 dosimetry quality audits (i.e., 102 of Co‐60 and 79 of linear accelerators) for teletherapy units installed at 22 different sites were performed from 1989 to 2015. The percent deviation between users' calculated/stated dose and evaluated dose (in the result of on‐site dosimetry visits) were calculated and the results were analyzed with respect to the limits of ± 2.5 % (ICRU "optimal model") ± 3.0 % (IAEA on‐site dosimetry visits limit) and ± 5.0 % (ICRU minimal or "lowest acceptable" model). The results showed that out of 181 total on‐site dosimetry visits, 20.44%, 16.02%, and 4.42% were out of acceptable limits of ± 2.5 % ± 3.0 %, and ± 5.0 %, respectively. The importance of a proper ongoing quality assurance program, recommendations of the followed protocols, and properly calibrated thermometers, pressure gauges, and humidity meters at radiotherapy hospitals are essential in maintaining consistency and uniformity of absorbed dose measurements for precision in dose delivery. PACS number(s): 87.50.cm, 87.50.sj, 87.50.up, 87.50.wj, 87.50.yk, 87.55.km, 87.55.Qr